PENGEMBANGAN PARIWISATA MENGGUNAKAN MODEL PENTAHELIX DI KABUPATEN BELU - Jemianus Yusuf A. V. Do Carmo; Novi Theresia Kiak; Maria Indriyani Hewe Tiwu Tiwu (Universitas Udayana, 2025)
In an effort to increasel tourism, the government is developing the tourism sectorl through the pentahelix collaboration. Many tourism objects in Belu Regency have the potential to be developed because of their uniqueness. The Belu Regency Regional Government seeks to develop tourisml through collaboration with variousl parties suchl as the Belu Regency Tourisml Office, academics, media, business actors and the community. However, it is not known to what extent the involved parties are involved in tourism development, thus, the problem formulationl in this research is how the tourism development strategy uses the pentahelix model in Belu Regency. The aiml of thisl research isl to explain and formulate a tourism development strategy using the model. pentahelix in Belu Regency. The research method usedl was descriptive qualitative. The conclusionl in this research is that the pentahelix model in tourism development in Belu Regency has not run optimally. This isl because collaboration between actors has not yet taken place considering that there is still a tendency for actors to work independently, apart from that there is stilll distrust between actors. Keywords: Pentahelix, Development, Tourism Potential